End-to-end test for lung SBRT: An Italian multicentric pilot experience. (December 2022) - Pallotta, S.; Calusi, S.; Marrazzo, L.; Talamonti, C.; Russo, S.; Esposito, M; Fiandra, C; Giglioli, F.R.; Pimpinella, M.; De Coste, V.; Bruschi, A.; Barbiero, S.; et al.
Highlights: Set-up of a Stereotactic Body Radiation Therapy (SBRT) e2e test. Multicenter validation of the e2e test. All participants were successful in performing the e2e test following the instructions. Abstract: Purpose: Set up a lung SBRT end-to-end (e2e) test and perform a multicentre validation. Material and methods: A group of medical physicists from four hospitals and the Italian Institute of Ionizing Radiation Metrology designed the present e2e test. One sub-group set up the test, while another tested its feasibility and ease of use. A satisfaction questionnaire was used to collect user feedback. Each participating centre (PC) received the ADAM breathing phantom, a microDiamond detector and radiochromic films. Following the e2e protocol, each PC performed its standard internal procedure for simulating, planning, and irradiating the phantom. Each PC uploaded its planning and treatment delivery data in a shared Google Drive. A single centre analyzed all the data. Results: The e2e test was successfully performed by all PCs. Participants' comments indicated that ADAM was well suited to the purpose and the protocol well described. All PCs performed the test in static and dynamic modes. The ratio between measured and planned point dose obtained by PC1, PC2, PC3, PC4 was: 0.99, 0.96, 1.01 and 1.01 (static track) and 0.99, 1.02, 1.01 and 0.94 (dynamic track). The gamma passing rates (3 % global, 3 mm) between planned and measured dose maps were 98.5 %, 94.0 %, 99.1 % and 94.0 % (static track) and 99.5 %, 96.5 %, 86.0 % and 94.5 % (dynamic track) for PC1, PC2, PC3 and PC4, respectively. Conclusions: An e2e test for lung SBRT has been proposed and tested in a multicentre framework. The results and user feedback prove the validity of the proposed e2e test.